Interchangeability of Fluconazole Drugs - N. D. Bunyatyan; B. B. Sysuev; E. A. Sokova; V. A. Evteev (Регуляторные исследования и экспертиза лекарственных средств, 2018)
Fluconazole – an antifungal agent belonging to the chemical class of triazole derivatives – is represented in the Russian pharmaceutical market by a large number of generic drugs. An important issue of rational pharmacotherapy is the demonstration of the reference and generic drugs’ equivalence with the aim of assessing their interchangeability. Therefore, the aim of this study was to analyse fluconazole drug dosage forms and routes of administration, as well as qualitative and quantitative composition of active substances and excipients in order to identify characteristics that may affect interchangeability. The analysis of the nomenclature and composition of fluconazole drugs was carried out based on the data contained in the National Register of Medicinal Products of the Russian Federation and the Reference Book of Medicines®. It was shown that the current nomenclature of fluconazole drugs includes the following types of products: for parenteral use, internal use, and topical use. The generic fluconazole drugs in the form of capsules differ from the reference Diflucan® in excipients, shelf life, and packaging. The fluconazole substance has a number of specific features, i.e. the presence of polymorphic modifications, their specific characteristics, and the influence of the process parameters and storage on their stability. It was revealed that in many cases the production of fluconazole capsules involved the use of substances purchased from two or more suppliers, which may lead to changes in quality and bioavailability during storage. The obtained data can be used in the future for optimisation of pharmaceutical development and evaluation of interchangeability of fluconazole drugs.